To love a king - Husk, Shona; Copyright Paperback Collection (Library of Congress); Copyright Paperback Collection (Library of Congress) (Naperville, Ill : Sourcebooks Casablanca, 2014)
"To keep the balance between good and evil at the court of Annwyn, Prince Felan ap Gwyn has two weeks to marry and take the crown. But he wants more than just power--he wants love; a love he once had but was too stubborn to hold on to. It took years for Jacqueline Ara to put her life back together after Felan abandoned her. And she doesn't want fairies back in her life--even if her heart still burns for him. With war in Annwyn looming and death bleeding into the mortal world, Felan and Jacquie will need to heal old wounds for one last gamble. It's all or nothing to save both worlds."-- Author's website.
Keywords: Aristocracy (Social class) -- Fiction; Man-woman relationships -- Fiction; Imaginary places -- Fiction; Love stories; Fantasy fiction; Fiction